Effect of Temperature on thermodynamic parameters and chemical properties at adsorption process nitrite on the Graphene Nano surface, density functional theory method - Ahmadi, Roya; Farajpour, Eysa (Ciência e Natura, 2015)
The project is comparing four types of calculation derived graphene. That two of these derivatives of graphene carbon nitrite connection created the difference is only in the state of Para and meta carbons connectivity state. But other derivatives first silicon-carbon alternatives in the meta and para position, then nitrite is added to the silicon. To evaluate the effect of silicon element to absorb energy and other thermodynamic parameters in the derivatives compared with them.